2017
DOI: 10.1159/000473872
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Chronic Staphylococcus aureus-Related Dermatoses with the Topical Endolysin Staphefekt SA.100: A Report of 3 Cases

Abstract: Staphylococcus aureus plays an important role in skin and soft tissue infections and contributes to the pathophysiology of complex skin disorders such as atopic dermatitis. Bacterial resistance against commonly used antibiotics has increased considerably in the last decades demanding alternative treatment approaches. We present 3 cases where patients with chronic and recurrent S. aureus-related dermatoses were successfully treated with Staphefekt SA.100. Staphefekt SA.100 is a recombinant phage endolysin for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 7 publications
2
96
0
4
Order By: Relevance
“…Several formulations, such as creams and gels, are currently commercialized under the Gladskin brand. It has recently been demonstrated that this product can successfully treat chronic and recurrent S. aureus -related dermatoses without generating bacterial resistance after long-term daily therapy ( 60 ).…”
Section: Therapeutic Efficacy Of Phage Lytic Proteinsmentioning
confidence: 99%
“…Several formulations, such as creams and gels, are currently commercialized under the Gladskin brand. It has recently been demonstrated that this product can successfully treat chronic and recurrent S. aureus -related dermatoses without generating bacterial resistance after long-term daily therapy ( 60 ).…”
Section: Therapeutic Efficacy Of Phage Lytic Proteinsmentioning
confidence: 99%
“…Staphylococcus species are opportunistic bacteria and the most pathogenic species. Strains of Staphylococcus aureus are able to colonize all tissues [1], secrete various enzymes and toxins [2][3][4] and cause various diseases including skin infections [5,6]. Microbial infections are normally treated using antibiotics, but the development of resistant strains award current antibiotics has become increasingly common which constitutes a growing public health problem, especially since these multi-resistant strains are no longer confined to hospital environments but are also found in the community [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Another example of current endolysin therapies is the topical use of the recombinant endolysin Staphefekt to treat skin flora dysbiosis caused by overgrowth of S. aureus. Staphefekt was able to decrease the load of S. aureus, restore the balance of the local flora, and clinically improve the condition in three patients (134) and has now progressed through to phase II clinical trials (135).…”
Section: Phage-derived Proteinsmentioning
confidence: 99%